2017
DOI: 10.1177/1478210316688355
|View full text |Cite
|
Sign up to set email alerts
|

Teachers, school choice and competition: Lock-in effects within and between sectors

Abstract: Neoliberal forces since the latter part of the 20th century have ushered in greater devolution in state schooling systems, producing uneven effects on the working conditions of teachers, commonly the largest segment of the public sector workforce. Within this context, this paper examines secondary teachers’ working conditions as they relate to the restructuring of the professional landscape that school choice reforms bring. Drawing illustrations from a qualitative study of teachers’ working experiences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…For example, teachers in Sweden are working in an environment characterized by reform agendas such as choice, privatization, marketization, competition as well as decentralization (Parding & Berg-Jansson, 2016;. Similar trends can be found in the Nordic context and elsewhere, such as Taiwan and Australia (e.g., Kamp, 2016;Huang, 2016;Parding, McGrath-Champ, & Stacey, 2017). Indeed, competence development 1 is an essential aspect of professional work.…”
Section: Discussionmentioning
confidence: 82%
“…For example, teachers in Sweden are working in an environment characterized by reform agendas such as choice, privatization, marketization, competition as well as decentralization (Parding & Berg-Jansson, 2016;. Similar trends can be found in the Nordic context and elsewhere, such as Taiwan and Australia (e.g., Kamp, 2016;Huang, 2016;Parding, McGrath-Champ, & Stacey, 2017). Indeed, competence development 1 is an essential aspect of professional work.…”
Section: Discussionmentioning
confidence: 82%
“…Another point in which teachers’ experiences have been argued to differ with regard to geographical context, from the Australian context, is in relationships with superiors (McGrath-Champ et al, 2019), with greater ‘care’ apparent particularly in remote areas, where ‘the nexus between work and life outside work is often unclear as so much of remote life is intertwined with the workplace – socially, professionally and physically’ (Brasche and Harrington, 2012: 120). In our own previous research in this context, we found that how teachers describe their conditions for work clearly links back to local and regional circumstances; a differentiation in working conditions was identified (Parding et al, 2017). A contribution made in this article is to further develop this body of work through a focus on the welfare sector professionals working in the education sector – the teachers.…”
Section: A Spatially Informed Frame Of Reference On Welfare Sector Prmentioning
confidence: 83%
“…As an example of welfare-sector professionals situated in changing governance contexts, teachers in Sweden work in a context that is characterised by decentralisation, as well as choice, privatisation, marketisation and competition. Similar trends can be found in the Nordic context and elsewhere, such as Taiwan and Australia (Kamp, 2016;Huang, 2016;Parding et al, 2017a). These governance changes can be assumed to influence teachers' working conditions, including conditions for learning and development [1].…”
Section: Introductionmentioning
confidence: 88%
“…However, these three transitions can take different shapes depending on context, such as regional or even local workplace levels. Based on this line of argument, we argue that it is important to take specific contexts into consideration when examining conditions for professionals' learning (Parding et al, 2017a;Parding et al, 2017b). We can understand why the line of arguments brought forward in the education and the workplace learning fields are not always what we see in practice assisted by the sociology of professions.…”
Section: Previous Research and Theoretical Frameworkmentioning
confidence: 98%